(untitled) (NOURA: Jurnal Kajian Gender dan Anak, 2022)
Along with the rapid development of the times and the flow of information technology whose existence is difficult to stop, the social order has shifted. One of them is the existence of women in the public space for work, there are pros and cons to the presence of women in the public space for work which is still continuing. For this reason, this study aims to see how the role of women in efforts to improve the family economy from the perspective of sharia economic law. This study uses qualitative research with a library approach. The results of the study show that sharia economic law does not prohibit women from being involved in the world of work with the first condition that a working woman must not leave her main duties as a wife and housewife. Second, it must obtain the consent of the husband/guardian. Third, do not work in a place where men and women mingle with each other. Third, do not do work that damages Muslimah’s personality. Fourth, working women must maintain their genitals and chastity.